The Effect of Seat Back Inclination on Spinal Alignment in Automotive Seating Postures - Sato, Fusako; Miyazaki, Yusuke; Morikawa, Shigehiro; Ferreiro Perez, Antonio; Schick, Sylvia; Brolin, Karin; Svensson, Mats (Frontiers in Bioengineering and Biotechnology, 2021)
Experimental studies have demonstrated a relationship between spinal injury severity and vertebral kinematics, influenced by the initial spinal alignment of automotive occupants. However, few studies have investigated spinal alignment of automotive occupants in a single posture. To investigate further, this study focused on seat back inclination, which is one of the seat configurations that may affect initial spinal alignment. The purpose of this study was to investigate the effect of seat back inclination on spinal alignments, comparing spinal alignments of automotive seating postures in the 20° and 25° seat back angle, and standing and supine postures. The spinal columns of 11 female and 12 male volunteers in automotive seating postures were scanned in an upright open magnetic response imaging system. Patterns of their spinal alignments were analysed using Multi-Dimensional Scaling presented in a distribution map. Spinal segmental angles were also measured using the imaging data. In the maximum individual variances in spinal alignment, a prominent relationship between the cervical and thoracic spinal alignment was found. Subjects with a more lordotic cervical spine had a pronounced kyphotic thoracic spine, whereas subjects with a straighter to kyphotic cervical spine had a less kyphotic thoracic spine. The gender difference in spinal alignment, for automotive seating postures, were almost straight cervical and less-kyphotic thoracic spine for the female subjects and lordotic cervical and more pronounced kyphotic thoracic spine for the male subjects. The most prominent influence of seatback inclination appeared in thoracic kyphosis, with increased angles for 25° seat back. The difference in thoracic kyphosis between the two seatback angles and between the seating posture with the 20° seat back angle and the standing posture were greater for spinal alignments with a lordotic cervical spine than for spinal alignments with a kyphotic cervical spine.